1998
DOI: 10.1294/jes.9.93
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Microbiological and Therapeutic Aspects of Glanders in Equines.

Abstract: The role of glanders therapy as an alternative to test and slaughter policy was investigated in 13 draught equines (1 horse, 2 mares and 10 mules). The disease was diagnosed clinically and confirmed by isolation of Burkholderia mallei on blood agar and sterile potato slices. Mallein test was positive in 6 (46.15 %) of the 13 animals. All isolates from the 13 equines were sensitive to chloramphenicol, danofloxacin, norfloxacin and co-trimoxazole whereas penicillin and cephalexin were the least effective in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 3 publications
3
31
0
2
Order By: Relevance
“…which might be accounted for higher prevalence of such infections in rainy season of the study. Lower temperature and humidity of winter months were less favorable for the growth and multiplication of tick vectors which might contribute to lower frequency of such diseases in the study population (Muhammad et al, 1999;Zahid et al, 2005). Salih et al (2008) found the highest number of ticks occur during the rainy season.…”
Section: Season-wise Prevalencementioning
confidence: 90%
“…which might be accounted for higher prevalence of such infections in rainy season of the study. Lower temperature and humidity of winter months were less favorable for the growth and multiplication of tick vectors which might contribute to lower frequency of such diseases in the study population (Muhammad et al, 1999;Zahid et al, 2005). Salih et al (2008) found the highest number of ticks occur during the rainy season.…”
Section: Season-wise Prevalencementioning
confidence: 90%
“…Oxytetracycline is adjunct to buparvaquone because in addition antitheilerial activity, it helps to ameliorate the pneumonic changes and curative for anaplasmosis which may occur concurrently (Khanna et al, 1983;Bagherwal, 1989;Dolan et al, 1992). Muhammad et al (1999) …”
Section: Resultsmentioning
confidence: 99%
“…In late or chronic cases which usually complicated with pulmonary disorders, hence using of antibiotics with Bupaquone was usually recommended (Mbwambo et al, 2006). Muhammad et al (1999) reported that oxytetracycline is also effective against schizon stage of Theileria and it helps to cure respiratory infection in cattle, as well as effective against other concurrent hemaoprotozoal and rickettsial infection in cattle. Hence, the present study was designed to study the clinical, hematological changes and therapeutic efficacy of Buparvaquone and Oxytetracycline against the natural infection of Theileria annulata in cattle.…”
Section: Page129mentioning
confidence: 99%
“…However, glanders is believed to be still endemic in Middle East, Northern Africa and Asia [5]. Outbreaks of glanders have also been reported from India and Pakistan [6,7].…”
Section: Introductionmentioning
confidence: 99%